Perancangan Film Pendek Gelebah melalui Teknik One-Shot dalam Membangun Representasi Hyperreality (Pendekatan Estetika Film) - Afandi, Haekal Ridho; Renzina, Yudha Delonix (Institut Seni Indonesia Yogyakarta, 2026)
Design of the Short Film “Gelebah” Using the One-Shot Technique to Construct a Representation of Hyperreality (A Film Aesthetics Approach). The design of the film Gelebah, featuring one-shot visuals, is a cinematic work that responds to a middle-aged man's profound longing for his mother's love, which subsequently triggers hallucinations. The researcher creates a cinematic impression representing human life that persists despite deep sorrow. The film is produced using one-shot and long-take techniques from start to finish to convey a seamless reality of life. This design results in a precise one-take shot production process for Gelebah and demonstrates the practical implementation of cinematography techniques, ensuring they move beyond mere theoretical concepts. The use of one-take shot in this film successfully creates a hyperreality phenomenon that blurs the distinction between the audience's reality and imagination. Visually, Gelebah utilizes camera movements such as following objects, eye-level angles, and a variety of shots ranging from wide shots to close-ups. The one-shot technique effectively directs the audience's emotions in alignment with the directorial vision and serves as a valid technical reference for studies on long-take and one-shot cinematography.